Knowledge mapping of the relationship between norepinephrine and memory: a bibliometric analysis - Song, Qi; Tan, Yaqian (Frontiers in Endocrinology, 2023)
Introduction: Memory is a fundamental cognitive function for successful interactions with a complex environment. Norepinephrine (NE) is an essential component of catecholamine induced by emotional arousal, and numerous studies have demonstrated that NE is a key regulator in memory enhancement. We therefore conducted a bibliometric analysis to represent the knowledge pattern of the literature on the theme of NE-memory relationship. Methods: The WOSCC database was selected to extract literature published during 2003-2022. The collected data of annual production, global cooperation, research structure and hotspots were analyzed and visualized. Results: Our results showed that research on the links between NE and memory displayed a considerable development trend over the last two decades. The USA had a leading position in terms of scientific outputs and collaborations. Meanwhile, University of California Irvine contributed the most publications. Benno Roozendaal and James McGaugh were the most prolific authors in this field, and Neurobiology of Learning and Memory had the highest number of publications on this topic. The research emphasis has evolved from memory-related diseases and brain regions, to neural mechanisms for different types of memory at neural circuit levels. Conclusions: Our bibliometric analysis systematically analyzed the literature on the links between NE and memory from a bibliometric perspective. The demonstrated results of the knowledge mapping would provide valuable insights into the global research landscape.